Examining the accuracy of density functional theory for predicting the thermodynamics of water incorporation into minerals: The hydrates of calcium carbonate - Demichelis, Raffaella; Raiteri, Paolo; Gale, Julian; Dovesi, R. (American Chemical Society, 2013)
The thermodynamics of water incorporation into calcium carbonate to form hydrates has been computed quantum mechanically using density functional theory (DFT). The structure of both the hydrated and the anhydrous phases are accurately reproduced by pure-DFT, hybrid Hartree–Fock/DFT, and DFT-D2 (long-range empirical correction). However, all of the aforementioned schemes fail to correctly reproduce the experimental energetics for the hydration process. In particular, functionals that provide reliable values for the anhydrous and low water content phases (calcite, aragonite, monohydrocalcite) fail to predict the energetics for the highly hydrated phase (ikaite) and vice versa, such that a comprehensive reliable study cannot be performed with a single method. Given that the available C6 parameters for the dispersive contributions in augmented DFT schemes typically are derived for atoms in molecular environments, we have refitted this parameter specifically for carbonates based on the relative enthalpy of aragonite versus calcite. This leads to a major improvement of the computed relative enthalpy and free energy of the anhydrous and hydrated phases.This paper therefore confirms that (i) the most widely used DFT schemes are unable to predict the energetics of reactions involving systems with very different structures or those that are characterized by different kinds of interactions; (ii) van der Waals interactions are important even in systems dominated by strong ionic and covalent interactions; (iii) using literature C6 parameters that have been derived for molecular systems can lead to significant errors for solid systems; and (iv) PBE-type functionals specifically tailored for solids are able to predict at least the stability order of two polymorphs and the sign of ?H and ?G of a reaction, despite the fact that long-range correlation effects are not explicitly included in their formulation.